GENRE-BASED DIGITAL STORYTELLING IN THE 21st CENTURY EDUCATION: A STUDENTS’ PERCEPTION - Nadia Tiara Antik Sari; Nahrowi Adjie; Gilang Rajasa; Nuur Wachid Abdul Madjid (Jurnal Sosioteknologi, 2021)
The present study is aimed at investigating the perception of elementary school pre-service teachers regarding the genre based digital story telling projects in their General English (GE) class. The benefits and challenges of digital storytelling projects have been studied by many researchers. However, perception of elementary school pre-service teachers of the issue is still rarely investigated. The data were collected from open and closed questionnaire to 47 elementary school pre-service teachers of a public university in West Java, Indonesia. In the second semester, they had a GE class (kelas Mata Kuliah Umum/MKU Bahasa Inggris). They were given two genre-based digital storytelling projects i.e., the digital descriptive and narrative text projects. The findings are further explained in relation to the 4Cs skill in 21st century education. It is found that genre-based digital storytelling projects improve the elementary school pre-service teachers’ communication, collaboration, creative thinking, and creativity skill. The pre-service teachers generally perceived the learning as meaningful, engaging, and enjoyable, supporting digital storytelling as a powerful media in the 21st century education.